Bio-efficacy of herbicides against different weed flora of wheat in central plain zone of Uttar Pradesh - Siddiqui, M.Z.; Yadav, R.A.; Khan, N.; Parihar, G.S.; Kumar, Arvind (Annals of Agricultural Research, 2016)
Wheat is the most widely cultivated crop among the cereals and ranks next to the rice in term of production. Wheat crop incurred heavy loss due to weed infestation, the most dominant weeds in wheat crop are Phalaris minor, Chenopodium album, Melilotus alba, Anagallis arvensis and Convolvulus arvensis etc. About 37% yield losses occurs due to grass weeds only. Conventional method of weed removal is costly as well as ineffective. Whereas, application of herbicides for controlling weeds have been found effective and economical in wheat crop. Results revealed that weeds prevailed through-out the crop period caused, on an average, yield reduction of 42%. The application of herbicides viz. clodinafop-propargyl (15%) + metsulfuron (1%), sulfosulfourn (75% WG) + metsulfuron methly (5% WG) and clodinafop-propargyl 15% WP @100% recommended dose (RDC) shows greater effect on control of Phalaris minor. clodinafop-propargyl (15%) + metsulfuron (1%) @ 100% RDC showed very effective against grasses as well as broadleaf weeds followed by SF-10 100% RDC and clodinafop-propargyl (15%) + metsulfuron (1%) @ 75% RDC, respectively. All the yield attributing character viz., spike weight (g), length of spike (cm), number of spikelets/spike and 1000-grain weight were also maximized under clodinafop-propargyl (15%) + metsulfuron (1%) (100% RDC) under herbicide application treatments. The weed free treatment provided maximum grain yield (50.06 q/ ha) followed by treatment where clodinafop-propargyl (15%) + metsulfuron (1%) (100% RDC) (49.13 q/ha) was applied.